High brilliance γ-ray generation from the laser interaction in a carbon plasma channel - Heppe, Christian; Kumar, Naveen (Frontiers in Physics, 2022)
The generation of collimated, high brilliance γ-ray beams from a structured plasma channel target is studied by means of 2D PIC simulations. Simulation results reveal an optimum laser pulse duration of 20 fs for generating photon beams of brilliances up to 1020 s−1mm−1mrad−2 (0.1 %BW)−1 with photon energies well above 200 MeV in the interaction of an ultra-intense laser (incident laser power PL ≥ 5 PW) with a high-Z carbon structured plasma target. These results are aimed at employing the upcoming laser facilities with multi-petawatt (PW) laser powers to study the laser-driven nonlinear quantum electrodynamics processes in an all-optical laboratory setup.